2021
DOI: 10.1001/jamanetworkopen.2021.12813
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Associated With Non-Guideline–Based Treatment of Kidney Cancer in the United States

Abstract: IMPORTANCE Significant demographic disparities have been found to exist in the delivery of health care. Demographic factors associated with clinical decision-making in kidney cancer have not been thoroughly studied. OBJECTIVE To determine whether demographic factors, including sex and race/ethnicity, are associated with receipt of non-guideline-based treatment for kidney cancer. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study was conducted using data from the National Cancer Database for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Notably, these disparities persisted in the era of targeted therapies and oral anticancer agents (OAAs) ( 5 ). Prior studies have highlighted potential drivers of these racial disparities, including inequitable access to health care ( 6 , 7 ), differences in disease biology ( 8 , 9 ), and variable adherence to guideline-based treatment ( 10 ). Sex- or gender-related disparities in RCC have also been described ( 11 ), with studies reporting differences in tumor biology at the time of presentation ( 9 , 12 , 13 ) and varying rates of treatment utilization ( 10 , 14 , 15 ) between males and females.…”
mentioning
confidence: 99%
“…Notably, these disparities persisted in the era of targeted therapies and oral anticancer agents (OAAs) ( 5 ). Prior studies have highlighted potential drivers of these racial disparities, including inequitable access to health care ( 6 , 7 ), differences in disease biology ( 8 , 9 ), and variable adherence to guideline-based treatment ( 10 ). Sex- or gender-related disparities in RCC have also been described ( 11 ), with studies reporting differences in tumor biology at the time of presentation ( 9 , 12 , 13 ) and varying rates of treatment utilization ( 10 , 14 , 15 ) between males and females.…”
mentioning
confidence: 99%
“…Similarly, in the setting of metastatic RCC, Patel et al, found that females were less likely to undergo a cytoreductive nephrectomy as compared to their male counterparts [137]. In a population-based cohort study using data from the National Cancer Database, females with localized renal masses were treated more aggressively than males, with consequent significantly higher risks of overtreatment [138]. Despite these data, there is no mention of any potential sex-related differences in access to care and type of treatment pattern by the latest international Guidelines [104].…”
Section: Treatmentmentioning
confidence: 99%
“…Patients without health insurance were more likely to be undertreated (as compared to clinical consensus RCC treatment guidelines) relative to those with private insurance (OR 2.63, p < 0.001), potentially reflecting the limited availability of therapies in resource-scarce medical settings [31]. Notably, however, these differences in treatment access have carried over to even higher volume cancer hospitals with more diverse patient/payor populations.…”
Section: Treatment Access As a Contributing Factor For Socioeconomic ...mentioning
confidence: 99%